USING ANIMATION FILMS TO IMPROVE THE ABILITY OF THE SECOND GRADE STUDENTS OF SMAN 1 BANTAN IN WRITING LEGEND - Zaharah, Fitria (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This classroom action research was aimed to know whether animation films could improve the ability of the second grade students of SMAN 1 Bantan in writing legend. The participants of this research were 26 students of class XI Science 2. The data was collected by using observation sheets, writing tests and field notes. The collected data was analyzed by statistical analysis by using SPSS version 20.0. The research finding indicated that using animation films as media could improve studentsâ ability in writing legend both at the first and second cycle. The result of pre-test showed the average score of studentsâ writing ability was 59.38. It improved to 70.33 on post-test 1 and 77.08 on post-test 2. The animation films help the students to understand the plot of the film and gave the students idea to write. This media could build the new atmosphere in the classroom that motivated the students to learn writing legend. The questions given after the students watched the film also guided the students in writing. All in all, this media could effectively improve the ability of the second grade students of SMAN 1 Bantan in writing legend.Keywords: Animation Films, Writing, Senior High School, Action Research